1996
DOI: 10.1161/01.cir.94.8.1948
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase and the Regulation of Central Vessel Caliber in the Fetal Rat

Abstract: We suggest that nitric oxide, generated by iNOS, plays a significant role in control of major vessel and ductus arteriosus caliber in the rat fetus. In regard to the nitrergic regulation of the circulation, the fetus is clearly different from the adult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…Instead, we found that TNFα and iNOS mRNA expression was significantly increased in the maternally LPS-injected DA compared with in the maternally PBS-injected DA. Bustamante et al showed that a NO inhibitor closed the LPS-induced PDA, 15 which is consistent with the findings of the present study. Therefore, we think that NO plays a primary role in PDA by LPS-induced infection.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Instead, we found that TNFα and iNOS mRNA expression was significantly increased in the maternally LPS-injected DA compared with in the maternally PBS-injected DA. Bustamante et al showed that a NO inhibitor closed the LPS-induced PDA, 15 which is consistent with the findings of the present study. Therefore, we think that NO plays a primary role in PDA by LPS-induced infection.…”
supporting
confidence: 93%
“…31 In the in vivo experiment by Vucovich et al, mice but not rats were treated, and newborn term gestation mice were injected with LPS at 30 min of age and then the DA was assessed after a 4-h period of observation. Therefore, the duration of LPS exposure was much shorter in their study than our and Bustamante's experiments, 15 where chronic inflammatory responses were observed. Thus, we suggest that maternal LPS administration is a suitable method to investi- …”
Section: Tumor Necrosis Factor α Inducible No Synthase and Tlr4 Mrnamentioning
confidence: 50%
See 1 more Smart Citation
“…7 Although prostaglandins (PGs) are considered the dominant vasodilators opposing ductal constriction in the later part of gestation, 6 Kajimura et al suggest an even greater complexity in the mechanisms regulating ductus arteriosus, wherein • NO also plays an critical role in ductal patency, particularly in the setting of maternal chorioamnionitis. 5 Consistent with work by Bustmante et al showing that injection of lipopolysaccharide (LPS) to pregnant dams inhibits postnatal decreases in the diameter of the ductus via mechanisms related to • NO release, 8 Kajimura et al show that LPS injection increases expression of inducible nitric oxide synthase (NOS), but not PG expression, in delayed closure of the ductus. Such basic science discoveries are consistent with notable clinical observations.…”
supporting
confidence: 58%
“…There is mounting evidence that NO has important vasodilatory action in the fetal circulation as it does in the adult (21). Despite the apparent role of both eNOS and iNOS in regulating the fetal circulation (21), initiation of L-NAME-induced limb disruption seems to be primarily dependent on eNOS inhibition.…”
Section: Tiboni Et Almentioning
confidence: 99%